2005
DOI: 10.1001/archpsyc.62.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Families at High and Low Risk for Depression

Abstract: The association between parental MDD and child diagnosis is moderated by grandparental MDD status. The rates of psychopathology are highest in grandchildren of parents and grandparents with a moderately to severely impairing depression. Anxiety disorders are the early sign of psychopathology in the young grandchildren. Early interventions in the offspring of 2 generations affected with moderately to severely impairing MDD seem warranted. This familial group may be the target for neuroimaging, genetic, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
313
2
15

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 396 publications
(360 citation statements)
references
References 58 publications
24
313
2
15
Order By: Relevance
“…This is especially so given that paternal depression and maternal antisocial behavior were not assessed and may have contributed in meaningful ways to the intergenerational transmission of risk. Furthermore, a multigenerational assessment of family history may be valuable as recent research has demonstrated moderating effects of grandparent psychopathology on grandchild symptom presentation (Weissman et al, 2005). However, missing data on family members beyond the parental generation presented an insurmountable challenge in the present study.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is especially so given that paternal depression and maternal antisocial behavior were not assessed and may have contributed in meaningful ways to the intergenerational transmission of risk. Furthermore, a multigenerational assessment of family history may be valuable as recent research has demonstrated moderating effects of grandparent psychopathology on grandchild symptom presentation (Weissman et al, 2005). However, missing data on family members beyond the parental generation presented an insurmountable challenge in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Yet symptom severity may be additionally informative, indicating the degree of genetic and/ or environmental loading. A recent study of depression across three generations of families indicated that illness severity, as measured by impairment, conferred greater risk of transmission to later generations (Weissman et al, 2005). Functional impairment increases incrementally with symptom severity (Judd et al, 2005).…”
mentioning
confidence: 99%
“…Complementary to the findings of studies where offspring are the affected proband, investigations of depressed parents and grandparents have also found increased risk of anxiety (Lieb et al 2002a ;Weissman et al 2005), depression and substance disorders in offspring (e.g. Lieb et al 2002a).…”
Section: Familialitymentioning
confidence: 91%
“…10 Different types of investigation, such as adoption, twins or high-risk studies, corroborate the pivotal role of the familial component in the etiology of major depression, probably through gene-environment interactions. 11 As for the adult population, it is believed that the incidence and recurrence of depressive episodes can be mediated or moderated by stress factors such as losses, neglect or abuse, conflicts, and frustrations.…”
Section: Epidemiologymentioning
confidence: 98%